Sosialisasi dan Pelatihan Pembuatan Ecobrick Sebagai Upaya Penanganan Sampah Plastik di Desa Grenden, Kecamatan Puger - wazirotus sakinah; Saifurridzal Saifurridzal; Wahyuni Mayangsari (Dedikasi:Jurnal Pengabdian kepada Masyarakat, 2021)
Grenden Village has the highest number of households in Puger District. Generally, the habit of the people there in managing their waste are throwing it into rivers and the sea. This is the main cause of flooding in that area. One of the efforts to reduce the production of plastic waste is ecobrick. Ecobricks products are the basic material for making tables, chairs, and building materials because they have the strength to withstand loads according to the specified weight. The youth in Grenden village are agents of change who are the object of service to tackle plastic waste in their area. This service activity has 3 stages, (1) socialization regarding the impact of plastic waste disposal in the waters and the introduction of ecobricks, (2) training on making ecobricks, and (3) marketing the results of ecobricks into e-commerce. Participants were very enthusiastic about being directly involved in filling ecobricks with plastic waste and were very confident that they would be able to make more ecobricks in the future by collecting the plastic waste they produce. This positive response is a small step for good changes for the environment, especially in Grenden village.